Monitoring and Managing BTK Inhibitor Treatment-Related Adverse Events in Clinical Practice - O’Brien, Susan M.; Brown, Jennifer R.; Byrd, John C.; Furman, Richard R.; Ghia, Paolo; Sharman, Jeff P.; Wierda, William G. (Frontiers in Oncology, 2021)
Acalabrutinib is a second-generation Bruton tyrosine kinase (BTK) inhibitor approved by the United States Food and Drug Administration for the treatment of adult patients with chronic lymphocytic leukemia (CLL)/small lymphocytic lymphoma, and mantle cell lymphoma (relapsed after 1 prior therapy); and by the European Medicines Agency for the treatment of adult patients with CLL or relapsed/refractory MCL. Long-term follow-up data from the phase 2 ACE-CL-001 trial demonstrated durable responses with a favorable safety profile and no new safety concerns with acalabrutinib monotherapy in treatment-naïve and relapsed/refractory patients with CLL. Adverse events (AEs) attributed to acalabrutinib in clinical practice are consistent with those reported in the pivotal phase 3 ASCEND and ELEVATE-TN studies. The most common AE associated with acalabrutinib treatment is headache of limited duration, which occurs in 22%–51% of patients; and is mainly grade 1–2 in severity, with only 1% of patients experiencing grade ≥3 headache. In addition, acalabrutinib is associated with a low incidence of atrial fibrillation. This perspective will address management of AEs related to acalabrutinib therapy.